Effect of the COVID-19 Pandemic Restrictions on Outcomes of HIV Care among Adults in Uganda - Izudi, Jonathan; Kiragga, Agnes; Kalyesubula, Philip; Okoboi, Stephen; Castelnuovo, Barbara (Medicine, 2022)
Uganda enforced several stringent restrictions such as night-time curfews, travel bans, school closure, and physical and social distancing among others that constituted a national lockdown to prevent the spread of the Coronavirus disease 2019 (COVID-19). These restrictions disrupted the delivery of health services but the impact on outcomes of human immunodeficiency virus (HIV) care has not been rigorously studied. We evaluated the effect of the COVID-19 pandemic restrictions on outcomes of HIV care among people living with HIV (PLHIV) aged ≥15 years in Kampala, Uganda. We designed a nonrandomized, quasi-experimental study using observational data retrieved from six large HIV clinics and used the data to construct two cohorts: a comparison cohort nonexposed to the restrictions and an exposed cohort that experienced the restrictions. The comparison cohort consisted of PLHIV commenced on anti-retroviral therapy (ART) between March 1, 2018, and February 28, 2019, followed for ≥1 year with outcomes assessed in March 2020, just before the restrictions were imposed. The exposed cohort comprised of PLHIV started on ART between March 1, 2019, and February 28, 2020, followed for ≥1 year with outcomes assessed in June 2021. The primary outcomes are retention, viral load testing, viral load suppression, and mortality. We employed inverse probability of treatment weighting using propensity score (IPTW-PS) to achieve comparability between the two cohorts on selected covariates. We estimated the effect of the restriction on the outcomes using logistic regression analysis weighted by propensity scores (PS), reported as odds ratio (OR) and 95% confidence interval (CI). We analyzed data for nine, 952 participants, with 5094 (51.2%) in the exposed group. The overall mean age was 32.7 ± 8.8 years. In the exposed group relative to the comparison group, viral load testing (OR, 1.68; 95% CI, 1.59–1.78) and viral load suppression (OR, 1.34; 95% CI, 1.110–1.63) increased while retention (OR, 0.76; 95% CI, 0.70–0.81) and mortality (OR, 0.75; 95% CI, 0.64–0.88) reduced. Among PLHIV in Kampala, Uganda, viral load testing and suppression improved while retention and mortality reduced during the COVID-19 pandemic restrictions due to new approaches to ART delivery and the scale-up of existing ART delivery models.
Keywords: COVID-19 lockdown; Impact of COVID-19; COVID-19 restrictions